Understanding the Impact of Spiritual Intelligence on Job Satisfaction -An Exploratory Approach wrt selected Automobile units in Delhi Capital Region - Prof. (Dr)Sanjeev Bansal, Dr.Vijit Chaturvedi, Dr.LK Dhillon (International Journal of Advanced Science and Technology, 2020)
Understanding the relevance and application of Spirituality at workplace and the benefits associated with respect to both employee and employer perspective it aims to understand role  of Spiritual Intelligence on Jobsatisfaction of employees employed in Automobile unitsIt aimed at assessing whether the dimensions of Spiritual intelligence are related with each other and whether it helps in improving overall Job Satisfaction or not. It was found from study revealed that all the aspects of Spiritual Intelligence are related with each other and that all the dimensions are contributive towards improving Job Satisfaction. The outcome suggests that if employees are trained and oriented for high spiritual intelligence and its unparallel need it will help both individuals and organization. It will help individuals to overcome their personal concerns and will improve professional relation and wellbeing thus improving their performance.